An INTEGRATED MODEL TO EXPLAIN EARNINGS QUALITY: FINANCIAL PERFORMANCE AS A INTERVENING - Herlina, Herlina; Santosa, R. Ery Wibowo A; Alfitri, Destiana Nur; Nugroho, Wawan Sadtyo (EconBank: Journal of Economics and Banking, 2023)
This study aims to empirically determine the relationship between intellectual capital and accounting conservatism on earnings quality with financial performance as an intervening variable. This study uses data from manufacturing companies listed on the Indonesia Stock Exchange during 2018-2021. The sample was selected using a purposive sampling method to produce 35 companies. The analysis technique in this research is Multiple Linear Regression Analysis with a path analysis model. Based on the outcomes of the study shows that intellectual capital has an effect on financial performance, accounting conservatism has no effect on financial performance, intellectual capital has an effect on earnings quality, accounting conservatism has no effect on earnings quality, financial performance has an effect on earnings quality, financial performance is not able to mediate the influence of intellectual capital on earnings quality, financial performance is not able to mediate the effect of accounting conservatism on earnings quality.